Struggle with the issue, not each other : using confrontation to harvest success - Porras, Jerry I. (Pearson Education Pub. as FTPress Delivers, 2010)
"This Element is an excerpt from Success built to last: creating a life that matters (ISBN: 9780132287517) by Jerry Porras, Stewart Emery, and Mark Thompson. How to use carefully calibrated, constructive confrontation to ignite your team's best, most passionate, most creative ideas"--Resource description page.